Microbial Selection and Survival in Subseafloor Sediment - Kirkpatrick, John B.; Walsh, Emily A.; D’Hondt, Steven (Frontiers in Microbiology, 2019)
Many studies have examined relationships of microorganisms to geochemical zones in subseafloor sediment. However, responses to selective pressure and patterns of community succession with sediment depth have rarely been examined. Here we use 16S rDNA sequencing to examine the succession of microbial communities at sites in the Indian Ocean and the Bering Sea. The sediment ranges in depth from 0.16 to 332 meters below seafloor and in age from 660 to 1,300,000 years. The majority of subseafloor taxonomic diversity is present in the shallowest depth sampled. The best predictor of sequence presence or absence in the oldest sediment is relative abundance in the near-seafloor sediment. This relationship suggests that perseverance of specific taxa into deep, old sediment is primarily controlled by the taxonomic abundance that existed when the sediment was near the seafloor. The OTUs that dominate at depth comprise a subset of the local seafloor community at each site, rather than a grown-in group of geographically widespread subseafloor specialists. At both sites, most taxa classified as abundant decrease in relative frequency with increasing sediment depth and age. Comparison of community composition to cell counts at the Bering Sea site indicates that the rise of the few dominant taxa in the deep subseafloor community does not require cell replication, but might simply result from lower mortality relative to competing taxa on the long timescale of community burial.